Holistic Integrative Pharmacy and disease control - Jiao GUO; Gang CHEN; Xiong LI; Ken CHEN (KeAi Communications Co., Ltd., 2020)
[Abstract]: As disease models are continually advancing, we could realize the "integration of knowledge and action" in pharmacy to prevent and treat diseases more effectively. This can only be done by advocating multi-domain integration. Holistic integrative pharmacy is guided by a holistic view and a new type of theory and practice system that broadens the field of pharmacy research through multidisciplinary approach. Comprehensively understanding the profound connotation of holistic integrative pharmacy and applying it to disease prevention and treatment will help to promote the development of modern pharmacy, reform pharmacy education, and improve people's health.